Knowledge engineering and knowledge management : 21st International Conference, EKAW 2018, Nancy, France, November 12-16, 2018, Proceedings /: 21st International Conference, EKAW 2018, Nancy, France, November 12-16, 2018, Proceedings. (2018) - Unknown
No abstract available